2018
DOI: 10.7554/elife.37963
|View full text |Cite
|
Sign up to set email alerts
|

SLC6A14, an amino acid transporter, modifies the primary CF defect in fluid secretion

Abstract: The severity of intestinal disease associated with Cystic Fibrosis (CF) is variable in the patient population and this variability is partially conferred by the influence of modifier genes. Genome-wide association studies have identified SLC6A14, an electrogenic amino acid transporter, as a genetic modifier of CF-associated meconium ileus. The purpose of the current work was to determine the biological role of Slc6a14, by disrupting its expression in CF mice bearing the major mutation, F508del. We found that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 83 publications
8
41
0
Order By: Relevance
“…Addition of Apical Arginine Plus Inhibitors of Arginase-Enhanced NO Production in Primary Bronchial Cultures Obtained from Non-CF and CF Donors. In our previous work, we showed that arginine is transported across the apical membrane of murine intestinal epithelia and converted to NO (Ahmadi et al, 2018). Now, we show that arginine uptake across the apical membrane of primary bronchial cultures (from nine donors) also leads to an increase in cytosolic NO in non-CF cultures (Fig.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Addition of Apical Arginine Plus Inhibitors of Arginase-Enhanced NO Production in Primary Bronchial Cultures Obtained from Non-CF and CF Donors. In our previous work, we showed that arginine is transported across the apical membrane of murine intestinal epithelia and converted to NO (Ahmadi et al, 2018). Now, we show that arginine uptake across the apical membrane of primary bronchial cultures (from nine donors) also leads to an increase in cytosolic NO in non-CF cultures (Fig.…”
Section: Resultssupporting
confidence: 60%
“…Our previous studies in mice expressing F508del-Cftr (Cftr F508del/F508del ) showed that elevations in cytosolic arginine increased nitric oxide (NO)-mediated signaling to the mutant Cftr protein to enhance its channel function (Ahmadi et al, 2018). We hypothesized that interventions aiming to enhance cytosolic arginine concentrations and NO signaling would also increase F508del-CFTR channel function in human respiratory epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…Ahmadi et al also conducted another study to determine the biological function of SLC6A14 in the murine gastrointestinal tract [16]. They first demonstrated that SLC6A14 is a major apical amino acid transporter in the murine colon.…”
Section: Slc6a14 Function In the Gastrointestinal Tractmentioning
confidence: 99%
“…SLC6A14, the protein encoded by this gene, belongs to the solute carrier family 6 and uses the energy provided by Na + and Cl − gradients to import and concentrate all neutral amino acids as well as the two cationic acids lysine and arginine into the cytoplasm of different cell types. Besides the genotype/phenotype associations, the biological mechanisms explaining the impact of SLC6A14 on intestinal and lung phenotypes of CF patients are beginning to be elucidated as evidenced by recent studies [15][16][17]. This review focuses on SLC6A14 in the context of CF, especially its involvement in the pathophysiology of CF lung and gastrointestinal disease.…”
Section: Introductionmentioning
confidence: 99%
“…The SLC6A14 gene product is a Na/Cl À À dependent transporter of neutral and cationic amino acids, particularly arginine, located at the apical membrane of epithelial cells. 41 Disruption of SLC6A14 expression markedly aggravates the intestinal obstruction phenotype in CF mice and is strongly associated with meconium ileus in CF newborns. 42 Not only do genes other than CFTR define disease expression, but recent studies have also revealed that genetic signals influencing the expression of a modifier gene such as SLC6A14 are tissue-specific and can be expressed remotely from the site of disease.…”
Section: Modifier Genesmentioning
confidence: 99%